2019
DOI: 10.1101/mcs.a004093
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of clinical BARD1 germline variants

Abstract: Germline pathogenic variants in BRCA1/2 account for one-third of familial breast cancers. The majority of BRCA1 function requires heterodimerization with BARD1. In contrast to BRCA1 , BARD1 is a low-penetrance gene with an unclear clinical relevance, partly because of limited functional evidence. Using patient-derived lymphoblastoid cells, we functionally characterized two pathogenic variants (c.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Our team also actively performs functional work in our laboratory. [35][36][37] It is imperative for genetics services to pool their resources and patients together to generate a larger database for analysis. This benefits the patient and healthcare system at large and serves to improve variant classification.…”
Section: Discussionmentioning
confidence: 99%
“…Our team also actively performs functional work in our laboratory. [35][36][37] It is imperative for genetics services to pool their resources and patients together to generate a larger database for analysis. This benefits the patient and healthcare system at large and serves to improve variant classification.…”
Section: Discussionmentioning
confidence: 99%
“…An extremely rare variant of BARD1 with strong CRC inheritance pattern, c.1811-2A > G, resulted in the removal of exon 9 due to exon skipping, which is part of the BRCT domain [ 105 ]. Missense mutations, BARD1 c.1217G > A p.Arg406Gln (rs587780014) and BARD1 c.1918C > A p.Leu640Ile (rs1553612535), were present in three patients with stage III or IV CRC diagnosed before the age of 50 [ 106 ]. As these mutations are located in or near the ANK and BRCT domains, etoposide treatment of patients’ lymphoblastoid cells did not hinder BARD1 and BRCA1 colocalization or RAD51 foci formation.…”
Section: Bard1 In Non-breast and Non-gynecological Cancersmentioning
confidence: 99%
“…Another pathogenic BARD1 variant, also affecting BRCT domains, has been described in a woman diagnosed with CRC [ 31 ]. In another study, the authors reported three patients diagnosed with CRC before the age of 50 years with variants of unknown significance (VUS) in the BARD1 gene, one of them in BRCT domains [ 32 ]. A deletion affecting exons 5–6 of the BARD1 gene has also been detected in a patient diagnosed with rectal adenocarcinoma in a study involving 1,058 unselected CRC cases [ 33 ].…”
Section: Discussionmentioning
confidence: 99%